Parents’ preferences for herbal supplements in managing functional gastrointestinal disorders - Ayşegül Bükülmez; Ayşegül Köroğlu; Melike Taşdelen Baş (BMC Complementary Medicine and Therapies)
Abstract Gastrointestinal diseases in children and adolescents lead to a considerable impairment of the quality of life of children and parents. Accordingly, there are considerable socio-economic consequences for the family and society. Parents concerned about their children may seek alternative treatments and opt for traditional herbal supplements. This study aimed to determine the utilization status and variety of herbal supplements by parents of children with functional gastrointestinal disorders. 216 study participants were given a socio-demographic questionnaire, a diagnostic questionnaire based on the ROME-IV criteria and a questionnaire with 20 herb names used in traditional treatments. 33.3% of parents reported using “ginger; Zingiber officinale” for their children who were infants and suffered from infantile regurgitation. The herb most preferred by parents for their children with functional gastrointestinal disorders in childhood and adolescence was “spearmint; Mentha spicata” (28.9%). 57.9% of the parents participating in the study stated that they preferred herbal supplements for their children. In addition, 40% of the participants stated that they use the herbs with the advice of the referral. As a result, it has been shown that parents tend to use herbs or herbal supplements, that they need to be educated in the use of these supplements, and that they need access to the right herb and to reliable supplements derived from the right herb.